Sources pour une histoire juridique de la folie en situation coloniale - Timothy Collier; Silvia Falconieri; Isabelle Thiebau; Alain Zasadzinski (Clio@Themis)
The article gives an account of the methodological discussions that were carried out within the framework of the AMIAF research project, the purpose of which was to identify sources permitting the writing of a legal history of madness in the context of French colonization. The article thus starts by taking a look at the sources undergoing scrutiny, in particular those kept by the colonial archives. The paper then moves on to discuss the implementation of tools which facilitate both the access to and the use of documentary collections by the scientific community, or by anybody interested in the subject, by providing feedback on the construction of the AMIAF digital library.